Minimizing energy consumption in refrigerated vehicles through alternative external wall. (January 2017) - Adekomaya, Oludaisi; Jamiru, Tamba; Sadiku, Rotimi; Huan, Zhongie
Abstract: Transporting fresh foods and raw agricultural produce have been widely acknowledged as a critical aspect of food chain. Raw fresh food must be conveyed at a low temperature conditions to preserve quality and prolong the shelf life of transported food. This paper takes an insight look at food transport system and proffers a sustainable ways of reducing energy consumption in diesel engine driven vapour compression system. Many studies have reported that 15% of world total energy is used in food preservation while some authors have predicted additional 2% annual increment of energy demand to sustain food chain. In the course of this study, the authors pragmatically identified sources of energy demand in food transport and maintained that the best approach to minimise energy consumption in refrigerated vehicles is to find a light weight and low thermal conductivity material as the external wall of refrigerated vehicles. This research is of high interest in view of continuous rise in earth temperature occasioned by emission of carbon monoxide from fossil fuel. The authors further showed that the usage of aluminium sheet as external wall of refrigerated vehicles reduces the longevity of insulation which increases heat infiltration into the cooling chamber thereby aggravating energy demand.